EVALUATION OF LAND SURFACE TEMPERATURE, VEGETATION DENSITY AND BUILT-UP LAND COVER CHANGES AFTER THE DEVELOPMENT OF THE BATANG INTEGRATED INDUSTRIAL ESTATE (KITB), CENTRAL JAVA - Nurhidayah; Ahmad Hadi Ma’ruf; Rina Kurniati; Kasiyati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The development of the Batang Integrated Industrial Estate (KITB) since 2020 has triggered large-scale land transformation that has the potential to affect environmental biophysical conditions, particularly land surface temperature (LST), vegetation density (NDVI), and built-up land cover (NDBI). This study aims to evaluate the spatial and temporal changes in these three parameters during the 2019–2024 period and to analyze the statistical relationships among these variables. The data used consist of Landsat 8 and Landsat 9 satellite imagery for the years 2019, 2021, 2023, and 2024, which were processed to derive LST using the mono-window method, NDVI through the NIR–Red band combination, and NDBI using the SWIR–NIR bands. Spatial analysis was conducted through the mapping of the distribution of each parameter, while statistical analysis included descriptive statistics, Pearson correlation, and linear regression. The results indicate that the development of KITB has produced significant thermal and ecological impacts. LST increased from approximately 23–32°C in 2019 to 28–38°C in 2024, with higher temperature concentrations observed in the industrial core area and active construction zones. NDVI experienced a decline in areas that previously consisted of moderate to dense vegetation, particularly in the southern and western parts of the industrial estate, as indicated by the shift in NDVI map colors from green to brownish-red. Meanwhile, NDBI values showed a dominant increase in 2023–2024, corresponding to the expansion of built-up areas within the industrial zone. The correlation results show a strong negative relationship between NDVI and LST (r < 0), indicating that vegetation loss contributes to the increase in surface temperature. Conversely, a positive relationship was identified between NDBI and LST, suggesting that the expansion of built-up land cover contributes to surface warming. Overall, these findings confirm that the development of KITB has triggered significant increases in land surface temperature and vegetation degradation, highlighting the importance of green space management and thermal mitigation strategies in rapidly developing industrial areas.